World Economy Winter 2019 - Global growth remains sluggish for the time being - Klaus-Jürgen Gern; Philipp Hauber; Stefan Kooths; Ulrich Stolzenburg (Kiel Institute for the World Economy (IfW), 2019)
World output growth has slowed further in the course of 2019. However, most recently signs of stabilization appeared, especially in emerging economies where expectations seem to have started to improve. Growth is supported by more expansive monetary policies in the advanced economies and - on the back of lower US interest rates - many emerging economies. Against this backdrop, we expect the world economy to gradually gain traction going forward. Growth is projected to remain modest, however, as the US economy will continue to lose momentum in 2020 and the trend of a gradual slowdown in China will persist. World output, measured at Purchasing Power Parities, is forecast to decline to 3.0 percent in 2019, the lowest rate of growth since the Great Recession in 2009, and increase only slightly to 3.1 percent in 2020. Thus we have revised downwards our forecasts for both this year and next by 0.1 percentage point compared with our September report. For 2021 we continue to expect growth of 3.4 percent. Substantially lower growth could result in the case of a further significant deterioration of the environment for international trade leading to an additional slowdown of investment. Downward risks to the forecast rise with the degree to which the weakness in industrial production feeds through into the services sector of the economy, which has so far been relatively resilient. – – Dynamik weiter verringert. Am aktuellen Rand zeichnet sich aber eine Stabilisierung der Konjunktur ab; in den Schwellenländern scheinen sich die Erwartungen bereits etwas aufzuhellen. Stützend wirkt eine Lockerung der Geldpolitik; sie ist in den fortgeschrittenen Volkswirtschaften wieder stark expansiv ausgerichtet, und niedrigere US-Zinsen haben es den Zentralbanken in den Schwellenländern erlaubt, die Zinsen auf breiter Front zu senken. Hinzu kommen in einigen Ländern spürbare Anregungen von der Finanzpolitik. Vor diesem Hintergrund dürfte die Weltwirtschaft allmählich wieder Tritt fassen. Der Produktionsanstieg bleibt aber verhalten, nicht zuletzt weil die bisher recht robuste US-Konjunktur zunächst noch an Fahrt verliert und auch die Expansion der chinesischen Wirtschaft sich in der Grundtendenz weiter leicht verlangsamt. Der Anstieg der Weltproduktion, gerechnet auf Basis von Kaufkraftparitäten, wird in diesem Jahr auf 3,0 Prozent zurückgehen, die geringste Rate seit der Großen Rezession im Jahr 2009. Im kommenden Jahr dürfte die Zuwachsrate mit 3,1 Prozent nur wenig höher ausfallen. Wir haben unsere Prognose vom September damit für 2019 und 2020 nochmals leicht - um jeweils 0,1 Prozentpunkte - reduziert. Für 2021 erwarten wir unverändert einen Zuwachs um 3,4 Prozent. Eine erheblich ungünstigere Konjunkturentwicklung könnte in dem Fall eintreten, dass sich die Rahmenbedingungen für den internationalen Handel weiter spürbar verschlechtern und das Investitionsklima zusätzlich belastet wird. Dieses Abwärtsrisiko ist umso größer, je stärker die Schwäche in der Industrie mit zunehmender Dauer auf die Aktivität in der übrigen Wirtschaft durchwirkt.
Keywords: 330; advanced economies; emerging economies; monetary policy